Preparation method of high-thermal-conductivity phase change energy storage material based on bubble jet oriented graphene nanosheet layer

By implanting expanded microspheres into the graphene sheet layer and using hot pressing technology to generate jets, the graphene nanosheet layer is highly oriented, combined with vacuum infusion technology, the problem of low thermal conductivity efficiency of phase change energy storage materials is solved, and high The preparation of graphene phase change energy storage materials with thermal conductivity and fast response significantly improves thermal conductivity and response speed.

CN119143121AActive Publication Date: 2024-12-17BEIHANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411144139.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2024-12-17
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

The thermal conductivity efficiency of existing phase change energy storage composite materials is low and the thermal response speed is needed. The two-dimensional structure of graphene requires that the framework structure has a high orientation to make full use of its excellent thermal conductivity.

Method used

The graphene sheet layer is wrapped on the expansion microspheres by modification of the expansion microspheres, and a high-pressure air bubble is generated and ruptured by a hot pressing device, which generates a jet to deflect the graphene nanosheet layer. Combined with vacuum-assisted perfusion technology, highly thermally conductive graphite is prepared. Alkenyl phase change energy storage composite material.

Benefits of technology

The high orientation of the graphene framework is achieved, and the in-plane thermal conductivity and response speed is significantly improved. It is low in cost and simple in preparation process, which is suitable for mass production and preparation of materials of different sizes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143121A_ABST
    Figure CN119143121A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a high-thermal-conductivity phase change energy storage material based on an air bubble jet oriented graphene nanosheet layer. High-pressure expanded microspheres are introduced into graphene, when the expanded microspheres are broken, air jet is generated by bubbles to enable graphene sheets to deflect so as to prepare a high-orientation graphene skeleton, then the graphene skeleton with high thermal conductivity is obtained through high-temperature graphitization treatment, and a phase change energy storage material is poured for multiple times by utilizing a vacuum-assisted pouring method, so that the phase change energy storage material is obtained. The graphene phase change energy storage composite material with high thermal conductivity is obtained. The high-thermal-conductivity graphene phase change energy storage material has the characteristics of fast response and high heat storage, the response time is shortened by 1 / 2 compared with that of a traditional commercial material, the maximum thermal conductivity can reach 152W / (m.K), the bulk phase change enthalpy value is up to 249kJ / L, and the thermal conductivity and the phase change enthalpy value can be adjusted according to different requirements. Therefore, the novel graphene phase change energy storage material has a great application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of composite materials, and in particular to a method for preparing a high thermal conductivity phase change energy storage material based on air bubble jet oriented graphene nanosheet layers. Background Art

[0002] The research on phase change energy storage technology began in the 20th century, initially focusing on the utilization of solar energy and heat storage in residential heating systems. With the development of technology, the application scope of this material has gradually expanded to cover many fields such as construction, transportation, and electronic manufacturing. This is because phase change energy storage materials have significant advantages in energy conservation and emission reduction, improving energy utilization efficiency, etc., and can effectively support the goal of sustainable development. In addition, the non-renewable and polluting nature of petroleum resources has brought serious environmental problems and concerns about resource depletion, such as global warming and air pollution, and this unsustainable energy model urgently needs to be transformed. Therefore, the development of efficient storage and conversion of clean energy is an urgent task.

[0003] Among the many current energy storage technologies, thermal energy storage technology shows great potential and prospects. This technology can store thermal energy in a high-capacity and large-scale manner. Thanks to the rapid development of materials science in recent years, thermal energy storage not only has high energy density and high conversion efficiency, but also achieves low cost. In particular, the application of phase change energy storage composite materials is particularly important. This material uses the endothermic or exothermic properties during the phase change process to release stored heat during peak electricity demand and store excess heat during low demand. This not only helps to balance the supply and demand of thermal energy, but also greatly improves the overall efficiency of energy utilization.

[0004] In the phase change energy storage composites currently being studied, a major technical challenge is to improve the thermal conductivity of these materials because they generally have low thermal conductivity. The key to solving this problem is to optimize the support portion of the composite material to achieve a faster thermal response speed. In this regard, graphene, a popular two-dimensional material, shows great potential because of its extremely high in-plane thermal conductivity (between 2000 and 5000 W / m·K). This material has been widely studied and applied to improve thermal conductivity. However, the unique two-dimensional structure of graphene causes its thermal conduction mode to be different from that of conventional materials, which requires that the skeleton structure of graphene has a high degree of orientation to fully utilize its excellent thermal conductivity properties. Summary of the invention

[0005] In view of the urgent need for phase-change energy storage composite materials with high thermal conductivity, the present invention provides a method for preparing a phase-change energy storage material with high thermal conductivity based on bubble jet-oriented graphene nanosheets. First, the expanded microspheres are modified so that the graphene sheets are wrapped on the expanded microspheres, and the expanded microspheres are made to produce high-pressure air bubbles through a hot pressing device. When the air bubbles are pressed down quickly, a jet is generated. The jet has a strong impact force, which can deflect the graphene nanosheets and make them highly oriented, thereby obtaining a graphene skeleton with high in-plane thermal conductivity. The phase change material is infused in a vacuum-assisted infusion manner to obtain a graphene-based phase-change energy storage composite material with high thermal conductivity. It is specifically carried out according to the following steps:

[0006] 1) Modification of expanded microspheres: The expanded microspheres are prepared into a dispersion with a mass fraction of 10%, placed in a water bath and heated to 50°C, triethylbenzyl ammonium chloride, octadecyl dimethylbenzyl ammonium chloride, benzalkonium chloride, etc. (one or more of them can be used) are added dropwise, and then kept warm for 3 hours for stirring and heating reaction;

[0007] 2) Preparation of graphene / expanded microsphere composite solid: The concentration of graphene slurry is 1wt%-10

[0008] wt% and modified expanded microspheres (the weight ratio of graphene to expanded microspheres is 1:1) are placed in a planetary stirrer and stirred at a rate of 500-2000r / min for 1h to form nano-dispersion of graphene sheets and modified expanded microspheres in the aqueous solution, and then the mixed dispersion is filtered to obtain a graphene / expanded microsphere composite solid, which is then dried in an oven at a temperature of 50°C;

[0009] 3) Preparation of highly oriented graphene skeleton: using a 500-mesh screen, the dried graphene / expanded microsphere composite solid is sieved into powder, and the powdered graphene / expanded microsphere composite solid is placed in a temperature-controlled molding device for heat preservation, so that the liquid in the microsphere undergoes a phase change, thereby expanding the microsphere to generate high-pressure air bubbles, and then the mold is quickly pressed down, the air bubbles burst, and a high-speed jet is generated, so that the graphene nanosheet layer is deflected, thereby obtaining a highly oriented graphene skeleton;

[0010] 4) Graphitization treatment of highly oriented graphene skeleton: the highly oriented graphene / expanded microsphere skeleton obtained in 3) is placed in a graphitization furnace and graphitized for 10-14 hours in an inert gas atmosphere to remove the internal expanded microspheres and repair the defects of the graphene nanosheets themselves. The temperature of the graphitization treatment is 2500°C-3200°C;

[0011] 5) Secondary densification of highly oriented graphene skeleton: placing the highly oriented graphene skeleton obtained in 4) in the molding mold of 3) and molding again to re-connect the graphene nanosheets that were originally not overlapped, thereby further reducing the microscopic interface thermal resistance;

[0012] 6) Infusing phase change energy storage material into the graphene skeleton: placing the graphene skeleton on the solid phase change material and putting it into a vacuum oven, evacuating the vacuum oven to -0.1MPa and then heating it to melt the phase change material. After melting, it is infused into the interior of the graphene skeleton under the action of vacuum negative pressure, and after natural cooling, a high thermal conductivity graphene phase change energy storage material is obtained.

[0013] Preferably, the amount of the expanded microspheres in the above step 1) is 10-50 g, and the amount of triethylbenzyl ammonium chloride is 1-5 g; (the expanded microspheres are polymer microspheres (such as methyl methacrylate) with volatile liquids (such as butane) sealed inside. By heating to a temperature above the phase transition temperature of the liquid, bubbles can be generated inside the microspheres, thereby expanding.

[0014] Preferably, the concentration of the graphene slurry in the above step 2) is 1wt%-10wt%;

[0015] Preferably, the temperature control range of the molding device in the above step 3) is 90-140°C, the insulation time is 5-30min, and the molding rate is 200-1000mm / min;

[0016] Preferably, the molding rate used for the secondary densification of the graphene skeleton in the above step 5) is 1-5 mm / min;

[0017] Preferably, the phase change material described in step 6) above includes but is not limited to highly refined paraffin wax, heptacosane, tetradecane, dioctadecane, dotriacontane, oxidized polyethylene wax, etc., and one or more of them can be used.

[0018] The beneficial effects of the present invention are as follows: 1. The graphene skeleton process prepared by the present invention is simpler than that prepared by the traditional method: compared with the method for preparing carbon foam, the method can prepare highly anisotropic graphene foam only by stirring, drying and hot pressing, and the cost is low. The carbon foam prepared by the traditional method requires high temperature and long time, and the prepared carbon foam is isotropic, which is difficult to meet the anisotropic use requirements. 2. The present invention highly orients the graphene foam by gas explosion: the present invention implants expandable microspheres inside the graphene sheet, fills the inside with gas by heating, and then presses down to make the microspheres break laterally to produce a strong airflow, so that the graphene nanosheets are radially oriented. 3. The samples prepared by the present invention can be batched and more flexible: the present invention only prepares highly oriented graphene foam by stirring, drying and hot pressing, so graphene foams of different sizes can be prepared according to different sample requirements, and the uniformity of its orientation degree is higher, which is a great improvement compared with the traditional preparation method. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a simulation diagram of expanded microsphere oriented graphene sheets;

[0020] Figure 2 is a SEM image of the graphene / expanded microsphere composite solid of Example 1;

[0021] Figure 3 This is an optical photograph of the high thermal conductivity graphene skeleton of Example 1. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0023] Embodiment 1:

[0024] The method for preparing the fast-response, high-orientation phase-change energy storage composite material described in this embodiment is specifically carried out according to the following steps:

[0025] 1) 20g of expanded microspheres (methyl methacrylate microspheres sealed with butane) were prepared into a dispersion with a mass fraction of 10%, placed in a water bath and heated to 50°C, 2g of triethylbenzyl ammonium chloride was added dropwise, and then kept warm for 3h and stirred and heated for reaction;

[0026] 2) placing 5wt% of graphene slurry and modified expanded microspheres (the weight ratio of graphene to expanded microspheres is 1:1) in a planetary stirrer and stirring at a rate of 500r / min for 1h to form nano-dispersion of graphene sheets and modified expanded microspheres in the aqueous solution, and then filtering the mixed dispersion to obtain a graphene / expanded microsphere composite solid, and drying it in an oven at a temperature of 50°C;

[0027] 3) using a 500-mesh screen, sieving the dried graphene / expanded microsphere composite solid into powder, placing the powdered graphene / expanded microsphere composite solid in a temperature-controlled molding device at 110° C. for 10 min, and pressing it with a bidirectional pressing head at a speed of 500 mm / min;

[0028] 4) placing the highly oriented graphene / expanded microsphere skeleton obtained in 3) into a graphitization furnace, and performing a graphitization treatment for 12 hours in an inert gas atmosphere to remove the internal polymer dispersant and expanded microspheres and repair the defects of the graphene nanosheets themselves, and the temperature of the graphitization treatment is 3000° C.;

[0029] 5) placing the highly oriented graphene skeleton obtained in 4) in the molding die of 3), and molding at a speed of 3 mm / min to obtain a highly thermally conductive graphene skeleton with a porosity of 80%. Molding again can re-lap the graphene nanosheets that were originally not overlapped, further reducing the microscopic interface thermal resistance;

[0030] 6) placing the graphene skeleton on polyoxyethylene paraffin and putting it into a vacuum oven, pumping the vacuum oven to -0.1MPa and then heating it to melt the polyoxyethylene paraffin, and then pouring it into the interior of the graphene skeleton under the action of vacuum negative pressure after melting, and naturally cooling to obtain a high thermal conductivity graphene phase change energy storage material.

[0031] The graphene phase change energy storage material prepared in this embodiment 1 has a height of 20 mm and a diameter of 200 mm.

[0032] This embodiment tests the in-plane thermal conductivity of the sample and obtains that the in-plane thermal conductivity of the fast-response high-orientation phase change energy storage composite material is 113W / (m·K), the latent heat of bulk phase change is 230kJ / L, the porosity is 95%, and the orientation factor is 0.66. Compared with the traditional graphene / organic phase change energy storage material, the thermal conductivity is increased by 159%, the orientation factor is increased by two times, and compared with the commercial phase change composite material, the porosity is increased by 15%, and the response speed is increased by 40%. At the same time, the energy storage material can be obtained by the processing center to obtain phase change energy storage materials of different shapes for application in complex environments.

[0033] Embodiment 2:

[0034] In the method for preparing the highly oriented phase-change energy storage composite material described in this embodiment, only the amount of expanded microspheres in step 1) is changed to 30 g, and the remaining steps are the same as those in embodiment 1.

[0035] The height of the graphene phase change energy storage material prepared in the second embodiment of the present invention is 20mm and the diameter is 200mm. In this embodiment, by increasing the amount of expanded microspheres, the number of air bubbles is increased, so that more jets are generated at different positions, more graphene nanosheets are deflected, and their orientation degree is improved. By testing the in-plane thermal conductivity of the sample, the in-plane thermal conductivity of the high thermal conductivity and high orientation phase change energy storage composite material is obtained to be 141W / (m·K), the latent heat of bulk phase change is 233kJ / L, the orientation factor is 0.78, and the open porosity is 95%. The increase in the amount of expanded microspheres in step 1) causes more graphene nanosheets to deflect, increases the orientation degree of the graphene skeleton, and thus increases the in-plane thermal conductivity of the high thermal conductivity and high orientation phase change energy storage composite material.

[0036] Embodiment three:

[0037] In the method for preparing the highly oriented phase-change energy storage composite material described in this embodiment, only the insulation temperature in step 3) is changed to 140° C., and the remaining steps are the same as those in the first embodiment.

[0038] The height of the graphene phase change energy storage material prepared in the third embodiment is 20mm and the diameter is 200mm. In this embodiment, by increasing the insulation temperature, the internal pressure of the expanded microspheres is increased, thereby increasing the impact force of the jet generated when the expanded microspheres rupture, making the degree of deflection of the graphene nanosheet layer greater, making the orientation degree of the graphene skeleton higher, and obtaining a high thermal conductivity and high orientation phase change energy storage composite material with an in-plane thermal conductivity of 121W / (m·K), a phase change latent heat of 231kJ / L, an orientation factor of 0.69, and an open porosity of 95%. The reason why the thermal conductivity is not greatly increased by increasing the temperature may be that the expanded microspheres ruptured prematurely at too high a temperature.

[0039] Embodiment 4:

[0040] In the method for preparing the high thermal conductivity and high orientation phase change energy storage composite material described in this embodiment, only the pressing speed in step 3) is changed to 700 mm / min, and the remaining steps are the same as those in the first embodiment.

[0041] The height of the graphene phase change energy storage material prepared in this embodiment 4 is 20mm and the diameter is 200mm. By increasing the downward pressure speed, the impact force on the expanded microspheres is increased, so that the jet speed generated is faster and stronger, and the deflection angle of the graphene nanosheet layer is larger. By testing the in-plane thermal conductivity of the sample, the in-plane thermal conductivity of the high thermal conductivity and high heat storage phase change energy storage composite material is obtained to be 125W / (m·K), and the latent heat of phase change is 223kJ / L, the orientation factor is 0.70, and the open porosity is 95%.

[0042] Embodiment five:

[0043] In the method for preparing the high thermal conductivity and high orientation phase change energy storage composite material described in this embodiment, only the heat treatment time in step 4) is changed to 14 hours, and the remaining steps are the same as those in the first embodiment.

[0044] The height of the graphene phase change energy storage material prepared in this embodiment 5 is 20mm and the diameter is 200mm. By testing the in-plane thermal conductivity of the sample, the in-plane thermal conductivity of the high thermal conductivity and high orientation phase change energy storage composite material is 142W / (m·K), and the latent heat of phase change is 226kJ / L, the orientation factor is 0.62, and the porosity is 95%. By changing the heat treatment temperature in step 4), it is to verify the effect of graphitization temperature on removing residual groups on the graphene surface and rearranging the carbon structure on the graphene surface.

[0045] Embodiment six:

[0046] In the method for preparing the high thermal conductivity and high orientation phase change energy storage composite material described in this embodiment, only the pressing speed in step 5) is changed by 50 mm / min, and the remaining steps are the same as those in the first embodiment.

[0047] The height of the graphene phase change energy storage material prepared in this embodiment six is ​​20mm and the diameter is 200mm. By testing the in-plane thermal conductivity of the sample, the in-plane thermal conductivity of the high thermal conductivity and high orientation phase change energy storage composite material is 121W / (m·K), and the latent heat of phase change is 232kJ / L, the orientation factor is 0.62, and the open porosity is 95%. By changing the pressing rate in step 5), it is to fill the pores sintered in step 4), so that the graphene nanosheets overlap each other and the skeleton is densified, thereby improving the in-plane thermal conductivity of the phase change energy storage composite material. As the pressing speed increases, the normal deflection of the graphene sheet occurs less, so the thermal conductivity will be improved.

[0048] Comparative Example 1:

[0049] In the method for preparing the fast-response, highly oriented phase-change energy storage composite material described in this comparative example, only the triethylbenzyl ammonium chloride in step 1) is replaced with Tween 80, and the remaining steps are the same as those in Example 1.

[0050] The height of the graphene phase change energy storage material prepared in this comparative example 1 is 20 mm and the diameter is 200 mm. This embodiment changes the type of modifier, thereby changing the surface charge quantity of the expanded microspheres, thereby changing the number of graphene nanosheets adsorbed on the surface. By testing the in-plane thermal conductivity of the sample, the in-plane thermal conductivity of the high thermal conductivity oriented phase change energy storage composite material is obtained to be 102 W / (m·K), the latent heat of bulk phase change is 232 kJ / L, the orientation factor is 0.67, and the open porosity is 95%.

[0051] Comparative Example 2:

[0052] In the method for preparing the fast-response, highly oriented phase-change energy storage composite material described in this comparative example, only the heat treatment temperature in step 4) is changed to 2200° C., and the remaining steps are the same as those in Example 1.

[0053] The height of the graphene phase change energy storage material prepared in this comparative example 2 is 20mm and the diameter is 200mm. By testing the in-plane thermal conductivity of the sample, the in-plane thermal conductivity of the fast response high heat storage phase change energy storage composite material is 91W / (m·K), and the latent heat of phase change is 226kJ / L, and the orientation factor is 0.67. Increasing the temperature of the heat treatment is to give more energy to the carbon six-membered ring, so that more carbon atoms complete the rearrangement reaction, reduce the defects of the graphene sheet, and improve its thermal conductivity.

[0054] Comparative Example 3:

[0055] In the method for preparing the high thermal conductivity and high orientation phase change energy storage composite material described in this comparative example, only the oxidized polyethylene wax in step 6) is replaced with vinyl acetate, and the remaining steps are the same as those in Example 1.

[0056] The height of the graphene phase change energy storage material prepared in this comparative example 3 is 20mm and the diameter is 200mm. By testing the in-plane thermal conductivity of the sample, the in-plane thermal conductivity of the high thermal conductivity and high orientation phase change energy storage composite material is 110W / (m·K), and the phase change latent heat is 249kJ / L, the orientation factor is 0.67, and the open porosity is 95%. Different phase change materials have different enthalpy values, and different phase change materials can be used according to different needs.

[0057] Comparative Example 4:

[0058] The steps of this comparative example are the same as those of Example 1 except that the expanded microspheres are not added.

[0059] In this embodiment, by testing the in-plane thermal conductivity of the sample, it is found that the in-plane thermal conductivity of the fast response high-oriented phase change energy storage composite material is 43W / (m·K), the bulk phase change latent heat is 211kJ / L, the open porosity is 67%, and the orientation factor is 0.21.

Claims

1. A method for preparing a high thermal conductivity phase change energy storage material based on bubble jet oriented graphene nanosheets, characterized in that: The following steps are involved: 1) Modification of expanded microspheres: The expanded microspheres containing volatile liquid are prepared into a dispersion with a mass fraction of 10%, placed in a water bath and heated to 50° C., triethylbenzyl ammonium chloride, octadecyl dimethylbenzyl ammonium chloride or benzalkonium chloride is added dropwise, and then kept warm for 3 h and stirred for heating reaction; 2) Preparation of graphene / expanded microsphere composite solid: placing a graphene slurry with a concentration of 1wt%-10wt% and modified expanded microspheres in a planetary stirrer and stirring at a rate of 500-2000r / min for 1h, the weight ratio of graphene to expanded microspheres is 1:1, so that the graphene sheets and the modified expanded microspheres form nano-dispersion in the aqueous solution, and then filtering the mixed dispersion to obtain a graphene / expanded microsphere composite solid, and drying it in an oven at a temperature of 50°C; 3) Preparation of highly oriented graphene skeleton: using a 500-mesh screen, the dried graphene / expanded microsphere composite solid is sieved into powder, and the powdered graphene / expanded microsphere composite solid is placed in a heated molding device for heat preservation, so that the liquid in the microsphere undergoes a phase change, thereby expanding the microsphere to generate high-pressure bubbles, and then the mold is quickly pressed down to rupture the bubbles, generating a high-speed jet, so that the graphene nanosheet layer is deflected, thereby obtaining a highly oriented graphene skeleton; 4) Graphitization treatment of highly oriented graphene skeleton: the highly oriented graphene / expanded microsphere skeleton obtained in 3) is placed in a graphitization furnace and graphitized for 10-14 hours in an inert gas atmosphere to remove the internal expanded microspheres and repair the defects of the graphene nanosheets themselves. The temperature of the graphitization treatment is 2500°C-3200°C; 5) Secondary densification of the highly oriented graphene skeleton: placing the highly oriented graphene skeleton obtained in 4) in the molding die of 3) and molding again to re-connect the graphene nanosheets that were originally not overlapped, thereby further reducing the microscopic interface thermal resistance; 6) Infusing phase change energy storage material into the graphene skeleton: placing the graphene skeleton on the solid phase change material and putting it into a vacuum oven, evacuating the vacuum oven to -0.1MPa and then heating it to melt the phase change material. After melting, it is infused into the interior of the graphene skeleton under the action of vacuum negative pressure, and after natural cooling, a high thermal conductivity graphene phase change energy storage material is obtained.

2. The method for preparing a high thermal conductivity phase change energy storage material based on bubble jet oriented graphene nanosheets according to claim 1, characterized in that: The amount of the expanded microspheres in step 1) is 10-50 g, and the amount of triethylbenzylammonium chloride is 1-5 g.

3. The method for preparing a high thermal conductivity phase change energy storage material based on air bubble jet oriented graphene nanosheets according to claim 1, characterized in that: The expanded microspheres are made of methyl methacrylate, and the volatile liquid contained therein is butane.

4. The method for preparing a high thermal conductivity phase change energy storage material based on air bubble jet oriented graphene nanosheets according to claim 1, characterized in that: The temperature control range of the molding device described in step 3) is 90-140°C, and the molding rate is 200-1000mm / min.

5. The method for preparing a high thermal conductivity phase change energy storage material based on air bubble jet oriented graphene nanosheets according to claim 1, characterized in that: The molding rate used for the secondary densification of the graphene skeleton described in step 5) is 1-5 mm / min.

6. The method for preparing a high thermal conductivity phase change energy storage material based on air bubble jet oriented graphene nanosheets according to claim 1, characterized in that: The phase change material described in step 6) includes at least one of highly refined paraffin wax, heptacosane, tetradecane, dioctadecane, dotriacontane, and oxidized polyethylene wax.

7. A high thermal conductivity phase change energy storage material of oriented graphene nanosheets prepared by the method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method and application of nano-graphite powder with heat storage and conduction functions

    CN114031957A

  • Annealing precision casting method and pattern material comprising thermally collapsible expanded micro globe

    JP1993084539A